Pengaruh Gaya Mengajar Guru, Penerapan Reward, dan Kecerdasan Emosional terhadap Keaktifan Belajar Ekonomi Siswa MAN 1 Banyumas (Business and Accounting Education Journal, 2022)
This study aims to analyze the effect of the teacher's teaching style, the application of rewards, and emotional intelligence on the economic activity of students at MAN 1 Banyumas. The research population was class XI students who took economics subjects as many as 217 students with a total sample of 141 students. Data was collected using a questionnaire and analyzed using multiple regression analysis. The results showed (1) the teacher's teaching style has a positive effect on learning activeness, (2) the application of rewards has a positive effect on student learning activeness, (3) emotional intelligence has a positive effect on student learning activeness.